Prevalence of premenstrual syndrome among students - Stress a potential risk factor - Himalini Nandakumar; MaheshKumar Kuppusamy; Lavanya Sekhar; Padmavathi Ramaswamy (Elsevier, 2023)
Background: Premenstrual syndrome (PMS) is a group of symptoms that occur prior to menstruation and disappear with its onset. This study aims to determine the prevalence and possible risk factors of PMS among the medical students. Methods: We conducted a cross sectional survey which includes 450 female health professional undergraduate and postgraduate students between the age group of 18-35years. A self-administered questionnaire for PMS and self-rating stress (perceived stress scale-PSS) was used to evaluate the prevalence and severity of the PMS. Results: The prevalence of PMS among the student was 76.35%. Prevalence of PMS was significantly higher among the participants of age group 18-21 years, hostellers, participants who reported irregular physical activity and participants with high stress levels. The most common psychological symptom of PMS reported was reduced social interaction, followed by irritability while the most common somatic symptoms were aches and pains - muscle pain followed by abdominal bloating. PSS levels were significantly higher in females with PMS as compared to females without PMS. Conclusion: This study suggests that stress is a potential risk factor in increasing the incidence of PMS among young girls. PMS can impact the academic performance and decrease quality of life of students. Thus, interventions such as yoga and mind relaxing techniques should be adopted to minimize stress levels and thus improve the quality of life among young females who experience PMS.